PENERAPAN HUKUM ASURANSI DALAM PERJANJIAN ASURANSI KENDARAAN BERMOTOR - tarto, sutarto (JURNAL ILMIAH LIVING LAW, 2015)
Purpose of this study is to analyze the legal liability insurer for the loss suffered by the insured in motor vehicle insurance and legal consequences arising in motor vehicle insurance agreement. The author uses a normative juridical research method, the law conceived as norms, rules, principles or dogmas. The results of this study indicate legal liability insurer for the loss suffered by the insured in motor vehicle insurance, namely the right to make demands on the underwriting third party to incur losses when the insured has received a claim for damages and legal consequences arising in motor vehicle insurance agreement is an agreement vehicle that has been made between the insured to the insurer may be canceled by the insurer.